Analysis of the Significance Value of the Muara Tembesi Old Town Area Based on Law No. 11 of 2010 as a Cultural Preservation Effort - Wulan Resiyani Wulan Resiyani; Agmeysa Rizqi Yudiseconda (UNIVERSITAS PGRI YOGYAKARTA, 2026)
This research is entitled